Job Transformation in the Digital Era: Social and Economic Perspectives - Haruni Ode; Sokha Dara; Rania Khatib (Yayasan Adra Karima Hubbi, 2025)
The rapid advancement of digital technology has significantly transformed the job market, affecting both social and economic structures. The shift from traditional employment to digital-based work models has created new opportunities while also posing challenges such as job displacement, skill gaps, and economic disparities. This study aims to analyze the transformation of jobs in the digital era from social and economic perspectives, highlighting the implications for workers and policymakers. This research adopts a qualitative approach using a literature review method. Various academic sources, including journal articles, reports, and case studies, were analyzed to identify trends and impacts of digitalization on employment. The study also examines government policies and corporate strategies in adapting to these changes. The findings indicate that digital transformation has led to increased job automation, the emergence of new professions, and shifts in workforce demand. While digitalization improves efficiency and economic growth, it also raises concerns about job security and the need for continuous upskilling. Socially, the digital divide has widened, affecting access to employment opportunities, particularly in developing regions. Economically, while some sectors thrive in the digital economy, others struggle to adapt, leading to labor market imbalances. In conclusion, job transformation in the digital era necessitates proactive measures from governments, businesses, and educational institutions. Policies should focus on digital literacy, reskilling programs, and inclusive economic strategies to mitigate negative impacts while maximizing benefits. Addressing these challenges will ensure a balanced and sustainable job market in the digital age.